Post hoc efficacy and safety analysis of insulin glargine/lixisenatide fixed- ratio combination in North American patients compared with the rest of world. Issue 1 (21st March 2019) - Dailey, George; Bajaj, Harpreet S; Dex, Terry; Groleau, Melanie; Stager, William; Vinik, Aaron
Abstract : Objective: To assess the efficacy and safety of iGlarLixi (titratable fixed-ratio combination of insulin glargine (iGlar) and lixisenatide) in patients with type 2 diabetes (T2D) living in North America (NA; USA and Canada) compared with the rest of the world (RoW). Research design and methods: Post hoc analysis included patient-level data from 509 sites/centers across two phase III trials: LixiLan-O (NCT02058147 ; insulin-naive patients; NA, n=371; RoW, n=796) and LixiLan-L (NCT02058160 ; inadequately controlled patients on basal insulin; NA, n=196; RoW, n=535). Efficacy outcomes were: change from baseline to Week 30 in glycated hemoglobin (HbA1c), postprandial glucose (PPG), PPG excursions, fasting plasma glucose (FPG) and body weight; proportion of patients achieving HbA1c <42 mmol/mol (<7.0%); proportion of patients achieving composite endpoint: HbA1c <42 mmol/mol (<7.0%), no weight gain or symptomatic hypoglycemia (blood glucose ≤3.9 mmol/L (≤70 mg/dL)). Safety endpoints included incidence of documented symptomatic hypoglycemia and gastrointestinal (GI) adverse events. Results: Significantly larger reductions (p≤0.003) in HbA1c from baseline to Week 30 were achieved with iGlarLixi, compared with iGlar or lixisenatide, in NA and RoW patients in LixiLan-O (iGlarLixi vs iGlar: −0.31 and −0.29, respectively; iGlarLixi vs lixisenatide: −0.84 and −0.69, respectively) and in LixiLan-L (iGlarLixi vs iGlar: −0.5 and −0.51, respectively). Documented symptomatic hypoglycemia was similar between NA and RoW patients. iGlarLixi resulted in significant weight benefits versus iGlar (change from baseline –1.58 and –1.29 kg for NA and RoW patients, respectively; p < 0.001). GI adverse events were similar for iGlarLixi and iGlar, but significantly higher for lixisenatide. Conclusions: iGlarLixi improved glycemic parameters versus iGlar or lixisenatide alone in both NA and RoW patients, with beneficial weight effects versus iGlar. iGlarLixi treatment responses, hypoglycemia risk and GI adverse events in NA patients were comparable with patients in the RoW. Trial registry: Clinicaltrials.gov NCT02058147 and NCT02058160 .-